1995
DOI: 10.1103/physrevd.51.2591
|View full text |Cite
|
Sign up to set email alerts
|

Quantum optics in static spacetimes: How to sense a cosmic string

Abstract: We study the influence of static gravitational fields on the spontaneous emission and the Lamb shift of atoms. To illustrate the procedure we consider a two-level atom coupled by a dipole interaction to a massless scalar quantum field in a general static Riemann space and work out the Einstein coefficient and the radiative energy shift. To treat an example, the general scheme is applied to a cosmic string spacetime. The possibility is discussed to detect, at least in principle, the cosmic string via the modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 15 publications
5
23
2
Order By: Relevance
“…The aforementioned examples are concerned with the atomic radiative properties in a Minkowski spacetime. In recent years, investigations concerning the atomic radiative properties in curved spacetimes have been carried out [15][16][17][18][19][20][21][22][23][24][25], and it is found that in certain curved spacetimes, behaviors of the atomic radiative properties similar to those in a bounded Minkowski spacetime occur, even when boundaries are absent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned examples are concerned with the atomic radiative properties in a Minkowski spacetime. In recent years, investigations concerning the atomic radiative properties in curved spacetimes have been carried out [15][16][17][18][19][20][21][22][23][24][25], and it is found that in certain curved spacetimes, behaviors of the atomic radiative properties similar to those in a bounded Minkowski spacetime occur, even when boundaries are absent.…”
Section: Introductionmentioning
confidence: 99%
“…The cosmic string spacetime is characterized by its nontrivial topological structure, and many quantum effects such as the vacuum fluctuations [39][40][41][42][43][44][45], atomic transition rates [15,22,44,46,47] and energy shifts [48] in this spacetime exhibit behaviors similar to those in a bounded flat spacetime. Here, we are interested in how the resonance interatomic energy is affected by the presence of a cosmic string and whether some boundarylike effects show up in the resonance interatomic energy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of authors have studied the Casimir effect and Casimir-Polder force in a more realistic situation where the atom interacts with electromagnetic vacuum fluctuations in the geometry of a straight cosmic string [35][36][37]. In this paper, we plan to study the spontaneous excitation and emission of a static atom immersed in a thermal bath of electromagnetic radiation in the vicinity of a straight cosmic string, where the atom is coupled to quantum electromagnetic fields rather than scalar fields in [38].…”
Section: Introductionmentioning
confidence: 99%
“…The simplest cosmic string spacetime is that of a static, straight and infinitely thin cosmic string, which can be regarded as a flat spacetime with a planar angle deficit. Quantum fields propagating in the cosmic string spacetime are inevitably influenced by the nontrivial topology, and many quantum effects, such as the vacuum expectations of stress-energy tensor [26][27][28][29][30][31], the Casimir-Polder effect [32], atomic transition rate [33][34][35][36], resonance interaction [37], and lightcone fluctuations [38,39] have been studied, which exhibit behaviors similar to those in a flat spacetime with a boundary. Therefore, it is also of interest to investigate the entanglement dynamics of two static atoms coupled with the vacuum fluctuations of massless scalar fields in the cosmic string spacetime, and compare the result with that in the Minkowski spacetime with a reflecting boundary [10,17,24].…”
Section: Introductionmentioning
confidence: 99%